POST TRAUMATIC STRESS DISORDER (GANGGUAN STRESS PASCA TRAUMA BENCANA) DI JAWA TENGAH - Mursid Zuhri (JURNAL LITBANG PROVINSI JAWA TENGAH, 2009)
Disaster represent occurence which is not desired, but intensity felt progressively mount in a few this the last year. Sacrifice handling which not yet maximal claim duty attention will and governmental responsibility and socialize. Research aim to: identify procedure identify Post Traumatic Stress Dissorder, handling of patient of Post Traumatic Stress Disorder and also the preventive effort and handling occurence in district of pasca disaster Central Java, identifying role of government agency non health and also institute the non government in the effort identifying, handling, prevention and penanggulangan occurence in disaster district, compiling picture of pattern of management of Integrated Post Traumatic Sress Disorder disaster district in Central Java. This research represent descriptive research qualitative mengunakan of method of survey,lokasi research of six regency that is Karanganyar, Pati, Cilacap, Brebes, Klaten And Banjarnegara. Datanya of primary and data Sekunder, way of data collecting [of] through indepth interview and perception to symptoms or obyek checked [by] and the direct interview with sacrifice. Fact team field need supplied knowledge about Assistive Post Traumatic Sress Disorder moment sacrifice overcome Post Traumatic Sress Disorder. Peran of Government agency of is non health and also non government in the effort identifying, handling have a lot of terlibat, monitoring and evaluate not yet dilakukan. Kebijakan government arranging role institute the non government in bearing with Standar of Procedure operational not yet there. Integrated management pattern not yet been [done/conducted]. Not yet there special peraturan/kebijakan from local government and also center arranging to hit pattern of management of pasca disaster integratedly. Raised recommendation, need of existence of activity of handling of soul health before and also hereafter the disaster, making as priority program in disaster handling by central government, Provinsi And Kabupaten/Kota, mengenalkan/sosialisasi disaster districts, in order to socialize can recognize existence of Post Traumatic Sress Disorder Befalling x'self, Need blazed the way a integrated handling start Puskesmas, integrate regency in handling preparation through hospital based, counselling to Kader Desa/Dukuh face, preventing existence of Post Traumatic Sress Disorder, need Handling Pattern. Base on society, countryside alert soul and base on hospital.